Peritonitis as a risk factor for long-term cardiovascular mortality in peritoneal dialysis patients: The case of a friendly fire? - Pecoits-Filho, Roberto; Yabumoto, Franciele M; Campos, Ludimila G; Moraes, Thyago P; Figueiredo, Ana E; Olandoski, Márcia; Shimakura, Silvia E; Barretti, Pasqual [UNESP] (Wiley, 2018)
Aim: Since the impact of peritonitis on long-term non-infectious mortality has not been investigated until the present, the aim of this study was to analyze the impact of peritonitis on long-term cardiovascular (CV) mortality in a large peritoneal dialysis (PD) cohort. Methods: The analysis was based on BRAZPD II, a national prospective cohort study that recruited patients in Brazilian centres from December 2004 to January 2011. Incident adult PD patients with at least 90 days on treatment were included in the analysis. Cardiovascular death occurring after a minimum of 30 days after a peritonitis episode was considered the primary endpoint. Cox regression analysis for time-dependent variables was used for the adjustments. Results: There were 2405 episodes of peritonitis in 5707 patients (48% males, 44% diabetes, 73% hypertensive). Patients with one episode of peritonitis presented a 22% increase in the hazard ratio of late CV mortality compared to those who never experienced peritonitis (HR1.22; CI95%1.01–1.47). Adjusted hazard for CV mortality showed a stepwise negative effect on survival for each additional peritonitis episode of infection: two episodes (HR1.78; CI95%1.31–2.42), three episodes (HR2.81; CI95%1.83–4.32) and four episodes (HR3.84; CI95%2.01–7.32). Conclusion: Peritonitis was an independent predictor of CV mortality and the frequency of peritonitis was strongly associated with an increase in this risk. This is the first study to demonstrate the impact of peritonitis on late cardiovascular mortality of PD patients, suggesting a link between acute inflammation and cardiovascular outcomes.
Keywords: cardiovascular mortality; inflammation; peritoneal dialysis; peritonitis; risk factor